Penerapan Arsitektur Neo Vernakular pada Bangunan Resort di Kawasan Pantai Sirombu, Nias Barat - Wiyu Fren Gulo; Rina Saraswaty Rina (Universitas Medan Area, 2026)
West Nias is a district located in the province of North Sumatra. Tourism in West Nias has good prospects and can still be developed optimally. Diverse tourist attractions are one of the potentials in the tourism sector in West Nias so classified as excellent in generating foreign exchange for the country. The stunning beauty of the islands The islands and beaches in West Nias are one of the attractions for tourists in exploring more about West Nias. This results in an increase in para tourist visitors from day to day. Of course, this is a significant increase in tourists gives rise to various problems. Problems in the West Nias Regency area one of which is the lack of accommodation for tourists. The design of this resort aims to support residential accommodation for tourists, as an internal effort improving the quality of tourism in the Sirombu beach area of West Nias by utilizing its natural potential. The design of the Tourist Center in the Sirombu coast area of West Nias is based on in the neo-vernacular approach, a construction concept consisting of modern elements and trying to adapt to the environment. The concept combines key aspects of form, usability and technology and integrated with the current environment.